Device and method for diffusion optical tomography - Fang Wai-Chi; Chen Tien-Ho; Kang Shih; Wu Shih-Yang; Cheng Ching-Ju (My University, 2013)
A device and method for diffusion optical tomography are disclosed. The device includes a sensing circuit with a plurality of light sources and sensors and an optical tomography element having a control unit, a computation unit and an image reconstruction unit. First, the computation unit constructs an image model of an object using optical parameters of the object, and performs decomposition on the image model. Then, the control unit instructs the light sources to emit light to the object, and receives a plurality of optical signals generated by the object in response to the light. Finally, the image reconstruction unit combines the optical signals and the decomposed image model and reconstructs an image of the object based on the combination of the optical signals and the decomposed image model.